آليات التصدي والدفاع عن القيم الثقافية المحلية للمجتمع الجزائري في ظل تحديات الثقافة الرقمية Mechanisms to address and defend the local cultural values of the Algerian society in light of the challenges of digital culture - لبيد عماد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
تهدف هذه الدراسة الى تسليط الضوء على دور التكنولوجيا الرقمية في اختراق الخصوصية الثقافية المحلية للمجتمع الجزائري، حيث ارتأت الدراسة عن تقسيم الموضوع إلى ثلاث محاور رئيسة؛ سنحاول من خلالها الوقوف عند خصوصية الثقافة المحلية للمجتمع الجزائري، وصولا إلى تجليات الثقافة الرقمية على القيم الثقافية للمجتمع، وأخيرًا الآليات المقترحة لتحقيق الأمن الثقافي في الجزائر في ظل تحديات الثقافة الرقمية ومن أهم النتائج التي توصلت إليها هذه الدراسة هي ضرورة التعامل مع التكنولوجية الرقمية بمنطق التعدد الثقافي في إطار التوازن والتكامل في ظل الفاعلية مع الثقافات الأخرى. Abstract: This study aims to shed light on the role of digital technology in penetrating the local cultural specificity of Algerian society, as the study decided to divide the issue into three main axes: We will try, through it, to stand up to the specificity of the local culture of the Algerian society, up to the manifestations of digital culture on the cultural values of society, and finally the proposed mechanisms to achieve cultural security in Algeria in light of the challenges of digital culture. Cultural within the framework of balance and complementarity under the agency with other cultures.